1984
DOI: 10.1088/0031-9155/29/9/002
|View full text |Cite
|
Sign up to set email alerts
|

The uptake and turnover of90Sr in the human skeleton

Abstract: In the United Kingdom, measurements have been made of the concentration of 90Sr in human bone from 1955 to 1970, and in human diet since 1958. A correlation of these two series of observations has enabled estimates to be made of (i) the fraction of the dietary intake of 90Sr that reaches the skeleton, (ii) the rate of turnover of 90Sr in the skeleton, and (iii) the way in which both these parameters vary with age. The results may be used to predict future levels of 90Sr in human bone from measurements of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…Blanchard 1966, Leggett et al 1982, Mangano et al 2003, Odum 1957, Papworth and Vennart 1984, Rickard 1964, Tolstykh et al 2003, Vose and Koontz 1959, Yamaguchi et al 2007). These studies provide much of the fundamental knowledge necessary for archaeological investigations of human mobility using strontium isotopes.…”
Section: Accepted For Publication In the Annals Of Human Biology 2010mentioning
confidence: 99%
See 1 more Smart Citation
“…Blanchard 1966, Leggett et al 1982, Mangano et al 2003, Odum 1957, Papworth and Vennart 1984, Rickard 1964, Tolstykh et al 2003, Vose and Koontz 1959, Yamaguchi et al 2007). These studies provide much of the fundamental knowledge necessary for archaeological investigations of human mobility using strontium isotopes.…”
Section: Accepted For Publication In the Annals Of Human Biology 2010mentioning
confidence: 99%
“…Residence times of different elements in the body can vary considerably and will be dependent on bone turnover rates, calcium intake, age and health status (Papworth and Vennart 1984, Rabinowitz 1991, Rabinowitz et al 1973). For example, Gulson et al (1999) showed that 50% of the lead circulating in the blood of pregnant women resident in Australia had been remobilised from old skeletal stores deposited prior to their migration to Australia.…”
Section: Accepted For Publication In the Annals Of Human Biology 2010mentioning
confidence: 99%
“…Other experimental studies have demonstrated that during pregnancy and breast-feeding strontium absorption is increased, reaching a maximum during breast-feeding. (Papworth & Patrick 1970;Papworth & Vennart, 1984) Absorption of strontium is dose dependant. Its bioavailability decreases with a lower dose, confirming that, just like calcium, absorption involves passive diffusion, independent of vitamin D levels, as well as saturable active transport, regulated by vitamin D and a facilitated diffusion.…”
Section: Pharmacological Characteristicsmentioning
confidence: 99%
“…In healthy adults, strontium plasma clearance varies between 9.4 and 11.7 ml/min, meanwhile the urinary clearance is between 4.0 and 5.4 ml/min. (Papworth & Vennart, 1984;Leeuwenkamp et al, 1989) In animal studies, the bone tissue strontium content decreased to approximately 50% at week 6 to 10 after stopping treatment. Renelic acid, given its high polarity, is poorly absorbed and its half-life in animals is about 1 hour, though it varies according to its absorption.…”
Section: Pharmacological Characteristicsmentioning
confidence: 99%
“…This observation is supported by the higher remodeling rate of bones and bone growth measured in younger children. As a consequence, the incorporation of 90 Sr in bones is faster (and higher) for young children than for adults (see also (Papworth and Vennart, 1984) for a discussion on the uptake and turnover of 90 Sr in the human skeleton). In this way, 90 Sr contamination of the environment and foodstuff will have a greater negative impact on children than on adults, leading to an absorbed dose in the marrow to age 70 about 30 times higher if 90 Sr is incorporated when less than one year old, compared to a similar ingestion at the age of 20 years (Papworth and Vennart, 1984).…”
Section: Sr In Bonesmentioning
confidence: 99%